2020
DOI: 10.4070/kcj.2019.0107
|View full text |Cite
|
Sign up to set email alerts
|

MiR-484 Protects Rat Myocardial Cells from Ischemia-Reperfusion Injury by Inhibiting Caspase-3 and Caspase-9 during Apoptosis

Abstract: Background and Objectives: To reveal the detail mechanism of miR-484 on myocardial ischemia-reperfusion (MI/R) injury. Methods: Rats model of MI/R injury was established based on control (Con; sham operate) group, ischemia-reperfusion (I/R) group, miR-484 treatment (miR) group, and I/R-negative control (IR-C) group, followed by pathological and interleukin (IL)-6, tumor necrosis factor (TNF)-α, and IL-1β expression evaluation. Then the myocardial apoptosis, as well as the expression of miR-484, caspase-3, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 28 publications
2
13
0
Order By: Relevance
“…A number of studies support the antiapoptotic function of miR-484 in a variety of cells. 18,[43][44][45][46][47] However, another previous study reported that the suppression of lncRNA H19 significantly reduced the viability of A549 cell viability, migration, and invasion but promoted apoptosis by targeting miR-484 in human lung cancer cells. 48 In this study, we found that the overexpression of miR-484 attenuated the apoptosis of RGCs induced by I/R damage; this opposed the effects arising from lncRNA Ttc3-209 treatment (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies support the antiapoptotic function of miR-484 in a variety of cells. 18,[43][44][45][46][47] However, another previous study reported that the suppression of lncRNA H19 significantly reduced the viability of A549 cell viability, migration, and invasion but promoted apoptosis by targeting miR-484 in human lung cancer cells. 48 In this study, we found that the overexpression of miR-484 attenuated the apoptosis of RGCs induced by I/R damage; this opposed the effects arising from lncRNA Ttc3-209 treatment (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Rats in antagomiR‐30a‐5p group were injected with antagomiR‐30a‐5p (1 × 10 3 mol/L) in myocardium at 24 hours before the establishment of I/R injury model. Meanwhile, the antagomiR‐Ctrl was injected into the myocardium at 24 hours before the establishment of I/R model in the antagomiR‐Ctrl group 13,14 . The myocardial infarct size was determined by staining with TTC (TGC, Shanghai, China).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the presence of miR-484 in the blood serum could be considered as a biomarker for both NSCLC [ 272 ] and colorectal cancer [ 188 ]. As well, miR-484 promotes neurogenesis by targeting PCDH19 [ 273 ], prevents ischemia-reperfusion injury by inhibiting CAS3 and CAS9 mediated apoptosis of myocardial cells in rats [ 274 ], creates resistance to sunitinib mediated therapy in metastatic renal carcinoma [ 189 ] and reverses cytidine deaminase axis (CDA)-mediated chemoresistance in breast cancer [ 190 ].…”
Section: Micrornas In the Regulation Of Ribosomal Protein Coding Mmentioning
confidence: 99%